Calcium thin film growth on a cyano-substituted poly(p-phenylene vinylene): Interface structure and energetics - Sharp, J. C.; Bebensee, Fabian; Baricuatro, J. H.; Steinrück, Hans-Peter; Gottfried, J. Michael; Campbell, C. T. (Journal of Physical Chemistry C, 2013)
The adsorption of Ca on poly[2-(2-ethylhexyloxy)-5-methoxy-1,4-phenylene cyanovinylene] (MEH-CN-PPV) at 130 and 300 K has been studied by adsorption microcalorimetry, X-ray photoelectron spectroscopy (XPS), and low-energy He ion-scattering spectroscopy (LEIS). The initial heat of adsorption of Ca on MEH-CN-PPV at 300 K is 436 kJ/mol. The heat of adsorption increases to 464 kJ/mol at ∼0.05 ML. We ascribe this initial heat to Ca abstracting cyano groups from the polymer backbone to make Ca(CN) clusters, plus a less important contribution due to Ca abstracting alkoxy groups to make Ca alkoxides. This is supported by XPS which shows the formation of new peaks in the N 1s and C 1s regions consistent with Ca(CN). There is also XPS evidence for Ca reacting with some of the ether groups to make Ca alkoxides at low coverage. Above 0.05 ML Ca coverage, the heat of adsorption decreases nearly exponentially to the sublimation enthalpy of bulk Ca solid (178 kJ/mol) by 5 ML. The observed behavior is attributed to the increasing probability of forming Ca nanoparticles and eventually a continuous solid Ca film on top of the reacted polymer. LEIS, which shows only a slow increase of the signal related to solid Ca, supports this model. Incoming Ca atoms undergo a kinetic competition between diffusing into the polymer to react with subsurface cyano or ether groups and forming or adding to three-dimensional Ca clusters on the surface. For studies done at 130 K, similar behavior is observed, with the heat of adsorption starting lower and decreasing more quickly to the heat of sublimation, already by 1.2 ML Ca coverage. This behavior along with the quicker growth of Ca on the surface of the polymer is attributed to the slower diffusion of Ca adatoms to subsurface cyano and ether groups. The effective thickness of "reacted" polymer (i.e., polymer which has lost its -CN groups and some alkoxy groups) is estimated to be 5.6 nm at 300 K but only 1.0 nm at 130 K. © 2013 American Chemical Society.

Calcium thin film growth on polyfluorenes: Interface structure and energetics - Sharp, J. C.; Feng, X. F.; Farrner, J. A.; Guo, Y. X.; Bebensee, Fabian; Baricuatro, J. H.; Zillner, Elisabeth; Zhu, J. F.; Steinrück, Hans-Peter; Gottfried, Michael; Campbell, C. T. (Journal of Physical Chemistry C, 2014)
The adsorption of Ca vapor on two polyfluorenes, poly(9,9-di-n-hexyl-2,7- fluorene) (PDHF) and poly(9,9-di-n-hexyl-2,7-fluorene vinylene) (PDHFV), has been studied by adsorption microcalorimetry, low-energy He ion scattering spectroscopy (LEIS), and ultraviolet and X-ray photoelectron spectroscopies (UPS and XPS) at surface temperatures between 130 and ∼400 K. At 300 K, the initial heat of adsorption of Ca on PDHF is 250 kJ/mol and on PDHFV is 315 kJ/mol. We ascribe this initial heat to Ca reacting with impurities or defects in the polymers. The heat of adsorption for both polymers decreases nearly exponentially to the sublimation enthalpy of bulk Ca solid (178 kJ/mol) by 0.75 ML. The observed behavior is attributed to the increasing probability of Ca finding and adding to solid three-dimensional Ca islands which nucleate and grow on the polymer surface and eventually grow into a continuous solid Ca film on top of the polymer. LEIS, which shows only a slow increase of the signals related to solid Ca, supports this model. Incoming Ca atoms are subject to a kinetic competition between diffusing into the polymer to react with subsurface defects or impurities versus adding to the three-dimensional Ca clusters on the surface. For studies done at 140 K, a similar behavior is observed, with the heat of adsorption starting lower and decreasing more quickly to the heat of sublimation, already by 0.1 ML Ca coverage. This behavior, along with the quicker growth of Ca on the surface of the polymer, is attributed to the slower diffusion of Ca adatoms to subsurface defects/impurities at 140 K than at 300 K. The opposite effect is observed when studied at 400 K. Calcium induces a downward band bending and work function decrease on both polymers, consistent with transfer of electrons from Ca to the polymers. © 2014 American Chemical Society.

Ethene adsorption and dehydrogenation on clean and oxygen precovered Ni(111) studied by high resolution x-ray photoelectron spectroscopy - Lorenz, Michael Peter Andreas; Fuhrmann, Thomas; Streber, R.; Bayer, Andreas; Bebensee, Fabian; Gotterbarm, Karin; Kinne, Martin; Tränkenschuh, Barbara; Zhu, J. F.; Papp, Christian; Denecke, R.; Steinrück, Hans-Peter (Journal of Chemical Physics, 2010)
The adsorption and thermal evolution of ethene (ethylene) on clean and oxygen precovered Ni(111) was investigated with high resolution x-ray photoelectron spectroscopy using synchrotron radiation at BESSY II. The high resolution spectra allow to unequivocally identify the local environment of individual carbon atoms. Upon adsorption at 110 K, ethene adsorbs in a geometry, where the two carbon atoms within the intact ethene molecule occupy nonequivalent sites, most likely hollow and on top; this new result unambiguously solves an old puzzle concerning the adsorption geometry of ethene on Ni(111). On the oxygen precovered surface a different adsorption geometry is found with both carbon atoms occupying equivalent hollow sites. Upon heating ethene on the clean surface, we can confirm the dehydrogenation to ethine (acetylene), which adsorbs in a geometry, where both carbon atoms occupy equivalent sites. On the oxygen precovered surface dehydrogenation of ethene is completely suppressed. For the identification of the adsorbed species and the quantitative analysis the vibrational fine structure of the x-ray photoelectron spectra was analyzed in detail. © 2010 American Institute of Physic

Formation of the calcium/poly(3-hexylthiophene) interface: Structure and energetics - Zhu, Junfa; Bebensee, Fabian; Hieringer, Wolfgang; Zhao, Wei; Baricuatro, J. H.; Farmer, Jason A.; Bai, Yun; Steinrück, Hans-Peter; Gottfried, Michael; Campbell, C. T. (Journal of the American Chemical Society, 2009)
The adsorption of Ca on poly(3-hexylthiophene) (P3HT) has been studied by adsorption microcalorimetry, atomic beam/surface scattering, X-ray photoelectron spectroscopy (XPS), low-energy He ion scattering spectroscopy (LEIS), and first-principles calculations. The sticking probability of Ca on P3HT is initially 0.35 and increases to almost unity by 5 ML. A very high initial heat of adsorption in the first 0.02 ML (625-500 kJ/mol) is attributed to the reaction of Ca with defect sites or residual contamination. Between 0.1 and 0.5 ML, there is a high and nearly constant heat of adsorption of 405 kJ/mol, which we ascribe to Ca reacting with subsurface sulfur atoms from the thiophene rings of the polymer. This is supported by the absence of LEIS signal for Ca and the shift of the S 2p XPS binding energy by -2.8 eV for reacted S atoms. The heat of adsorption decreases above 0.6 ML coverage, reaching the sublimation enthalpy of Ca, 178 kJ/mol, by 4 ML. This is attributed to the formation of Ca nanoparticles and eventually a continuous solid Ca film, on top of the polymer. LEIS and XPS measurements, which show only a slow increase of the signals related to solid Ca, support this model. Incoming Ca atoms are subject to a kinetic competition between diffusing into the polymer to react with subsurface thiophene units versus forming or adding to three-dimensional Ca clusters on the surface. At ∼1.6 ML Ca coverage, Ca atoms have similar probabilities for either process, with the former dominating at lower coverage. Ultimately about 1.6 ML of Ca (1.2 x 10 atoms/cm) reacts with S atoms, corresponding to a reacted depth of ∼3 nm, or nearly five monomerunit layers. Density-functional theory calculations confirm that the heat of reaction and the shift of the S 2p signal are consistent with Ca abstracting S from the thiophene rings to form small CaS clusters. © 2009 American Chemical Society.

Interface formation between calcium and electron-irradiated poly(3-hexylthiophene) - Bebensee, Fabian; Zhu, Junfa; Baricuatro, J. H.; Farmer, Jason A.; Bai, Yun; Steinrück, Hans-Peter; Campbell, C. T.; Gottfried, Michael (Langmuir, 2010)
The adsorption of Ca on electron-irradiated poly(3-hexylthiophene) (P3HT) surfaces at 300 K (E = 100 eV) has been studied by adsorption microcalorimetry, atomic beam/surface scattering, X-ray photoelectron spectroscopy (XPS), and low-energy He ion scattering spectroscopy (LEIS). The results are compared to previous studies of Ca adsorption on pristine P3HT. The major structural effect of electron irradiation is a substantial increase in the fraction of unsaturated carbon atoms, probably a result of electron-induced hydrogen abstraction from the hexyl chains and formation of new C=C double bonds. No loss of sulfur was observed. The combined XPS, LEIS, and calorimetry data indicate that the reaction and growth behavior of Ca on P3HT surfaces is not significantly affected by this electron damage, apart from an increased sticking probability at low coverages. The sticking probability of Ca on the irradiated P3HT is initially 0.63, compared to 0.36 on the pristine surface. It increases with coverage, approaching unity between 4 and 5 ML. The heat of adsorption stays nearly constant at 405 kJ/mol up to a coverage of 0.6 ML, which is ascribed to Ca diffusing below the surface and forming CaS clusters by abstraction of sulfur from the thiophene rings, based on XPS and LEIS data. The heat of adsorption then decreases gradually until it reaches the heat of sublimation of bulk Ca, 178 kJ/mol, by 4 ML; this is attributed to the formation of 3D Ca islands on top of the polymer, which eventually coalesce into a continuous Ca film by 11 ML. The heat of reaction versus coverage and the ultimate depth up to which the Ca atoms react with the polymer thiophene groups (∼3 nm) are nearly independent of electron damage, except for a difference in the heat of adsorption below 0.1 ML associated with defects or impurities. The increase in initial sticking probability caused by electron damage is attributed to stronger bonding of Ca adatoms to unsaturated versus saturated hydrocarbons. These very weakly held Ca adatoms are transient precursors to the two reactions which dominate the measured heat of adsorption (reaction with thiophene units and Ca cluster formation), but they can also desorb in this three-path kinetic competition. Mass spectrometer data show that these precursors have longer surface residence times on the electron-damaged surface. © 2010 American Chemical Society.

Toward well-defined metal-polymer interfaces: Temperature-controlled suppression of subsurface diffusion and reaction at the calcium/poly(3- Hexylthiophene) interface - Bebensee, Fabian; Schmid, Martin; Steinrück, Hans-Peter; Campbell, C. T.; Gottfried, Michael (Journal of the American Chemical Society, 2010)
The thickness of the reaction zone at the interface between calcium and regioregular poly(3-hexylthiophene), which is one of the best performing metal/polymer combinations in photovoltaic devices, depends critically on the temperature of the polymer during the initial phase of metal deposition. It is shown that deposition at 130 K reduces the thickness of the reaction zone, an effect that also persists after warming to room temperature. © 2010 American Chemical Society.